Конверсія етанолу до н-бутанолу на мідьвмісних каталізаторах з розділенням продуктової суміші - Varvarin, Anatoliy M.; Prudius, Svitlana V.; Zinchenko, Oleksii Yu.; Levytska, Svitlana I.; Shchutskyi, Igor V.; Brei, Volodymyr V. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2025)
Article presents the results on vapor-phase condensation of ethanol to n-butanol 2СН5ОН = С4Н9ОН + Н2О on the copper-containing catalysts. A sequential two-reactor scheme was applied using the developed supported catalyst for Guerbet reaction in first reactor (245 °C/0.6 MPa) and an industrial Cu-containing catalyst for hydration of the product mixture in second reactor (160 °C/0.6 MPa). Previously, in 2014, the process was tested by us on a pilot instalation with processing of 4 kg of bioethanol per hour. Now we have developed a new Guerbet-supported catalyst and replaced the hydrogenation catalyst. The main product is n-butanol, the content of which in the hydrogenated product mixture reaches 19 wt. % at ethanol conversion of 30 % in one pass at a catalyst loading of 12 mmol С2Н5ОН/gcat/h. When the catalyst load is doubled, the butanol content decreases to 11 %, but less impurities are formed. The process of separating the product mixture was simulated using the Aspen HYSYS v12 program and the material and heat balances of the proposed ethanol → butanol process were calculated. The process flow chart includes a reactor unit and 4 separation sections: preliminary separation, separation of light products (ethyl acetate, methyl ethyl ketone), dehydration of recycled ethanol, and a heavy products separation section operating under vacuum. A total the separation scheme includes 15 distillation columns, which can provide the separation of such commercial products as butanol-1, butanol-2, ethyl acetate, butyl acetate, methyl ethyl ketone, butyl butyrate and 2-ethylhexanol with a purity of 99.9 wt. %. A butanol production installation requires a total steam consumption of 8.4 t/t of ethanol, which is equivalent to 630 Nm3/t of natural gas, and electricity of 171 kWh/t of ethanol.